Demographic and clinical correlates of acute and convalescent SARS-CoV-2 infection among patients of a U.S. emergency department - Laeyendecker, Oliver; Hsieh, Yu-Hsiang; Rothman, Richard E.; Dashler, Gaby; Kickler, Thomas; Fernandez, Reinaldo E.; Clarke, William; Patel, Eshan U.; Tobian, Aaron A.R.; Kelen, Gabor D.; Quinn, Thomas C.; Schmidt, Haley A.; et al. (The American journal of emergency medicine, 2021)
Emergency Departments (EDs) have served as critical surveillance sites for infectious diseases. We sought to determine the prevalence and temporal trends of acute (by PCR) and convalescent (by antibody [Ab]) SARS-CoV-2 infection during the earliest phase of the pandemic among patients in an urban ED in Baltimore City. We tested remnant blood samples from 3255 unique ED patients, collected between March 16th and May 31st 2020 for SARS-CoV-2 Ab. PCR for acute SARS-CoV-2 infection from nasopharyngeal swabs was obtained on any patients based on clinical suspicion. Hospital records were abstracted and factors associated with SARS-CoV-2 infection were assessed. Of 3255 ED patients, 8.2% (95%CI: 7.3%, 9.2%) individuals had evidence of SARS-CoV-2 infection; 155 PCR+, 78 Ab+, and 35 who were both PCR+ and Ab+. Prevalence of disease increased throughout the study period, ranging from 3.2% (95%CI: 1.8%, 5.2%) PCR+ and 0.6% (95%CI: 0.1%, 1.8%) Ab+ in March, to 6.2% (95%CI: 5.1%, 7.4%) PCR+ and 4.2% (95%CI: 3.3%, 5.3%) Ab+ in May. The highest SARS-CoV-2 prevalence was found in Hispanic individuals who made up 8.4% (95%CI: 7.4%, 9.4%) of individuals screened, but 35% (95%CI: 29%, 41%) of infections (PCR and/or Ab+). Demographic and clinical factors independently associated with acute infection included Hispanic ethnicity, loss of smell or taste, subjective fever, cough, muscle ache and fever. Factors independently associated with convalescent infection were Hispanic ethnicity and low oxygen saturation. The burden of COVID-19 in Baltimore City increased dramatically over the 11-week study period and was disproportionately higher among Hispanic individuals. ED-based surveillance methods are important for identifying both acute and convalescent SARS-CoV-2 infections and provides important information regarding demographic and clinical correlates of disease in the local community.